Adherence to Essential Newborn Care Practices Among Nurses and Midwives in the Tamale Metropolis of Ghana - Babakyirenaah, N. (University of Ghana, 2020)
Newborn mortality is a canker in society robbing couples off their happiness and dreaded situations which affects mothers globally for carrying a pregnancy to term only to lose your baby due to preventable conditions. This devastating situation has left many mothers worried about childbirth most especially in LMICs. To avert and decrease the newborn morbidity and mortality numbers, WHO has recommended essential newborn care practices (ENCP). However, adherence to protocols in Ghana is generally low. Nurses and midwives adherence to ENCP is essential in the delivery of care to mothers and their newborns. Hence, the study to investigate Nurses and Midwives' adherence to ENCP in the Tamale Metropolis using the decomposed theory of planned behaviour (DTPB) as an organising framework. A quantitative study using a descriptive cross-sectional design was employed, and a multistage method of sampling techniques was used to gather a sample size of 330 nurses and midwives. Simple random sampling techniques were employed in the recruitment of respondents. Descriptive and inferential statistics thus, correlation, regression and mediation analysis in the statistical package for social science (SPSS) version 21.0 software were used to analyse data. The study findings revealed that nurses and midwives had positive attitudes, good subjective norm, positive PBC, positive behavioural intention and good behaviour (adherence) towards ENCP. The results indicated a positive relationship between attitude, subjective norm, PBC, behavioural intention and their behaviour. Also, their PBC and behavioural intention predicted their behaviour (adherence).Therefore, to ensure high life expectancy of newborns and their mothers there should be conclusive response to ENCP thereby ensure adherence to these protocols at each stage of the care setting
MPhil. Nursing
Keywords: Ghana; Newborn mortality; Childbrith; Tamale Metropolis; Essential newborn care practices; Decomposed theory of planned behaviour